2002
DOI: 10.1002/cncr.10417
|View full text |Cite
|
Sign up to set email alerts
|

Increased proliferative activity caused by loss of p21WAF1/CIP1 expression and its clinical significance in patients with early‐stage gastric carcinoma

Abstract: Der Anglerfisch‐Katalysator: Die Aktivierung von Anthracenen durch Aminokatalyse (siehe Schema) ermöglicht [4+2]‐Cycloadditionen mit gleichzeitigem Aromatizitätsverlust bei Raumtemperatur und niedriger Katalysatorkonzentration. Eine hoch enantioselektive Diels‐Alder‐Reaktion von Anthracenen mit Nitroalkenen als Dienophilen wurde ebenfalls entwickelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
3
5
0
3
Order By: Relevance
“…Other clinicopathological factors, including lymph node involvement and depth of invasion have not been found to correlate with Ki-67 index [18,19]. Like other researchers [2,[19][20][21][22][23], we found a statistically significant correlation of Ki-67, PCNA and MCM2 PI in advanced gastric cancer with local lymph node involvement. The mean proliferation indices for Ki-67 and PCNA were higher in gastric cancer with local lymph node involvement.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Other clinicopathological factors, including lymph node involvement and depth of invasion have not been found to correlate with Ki-67 index [18,19]. Like other researchers [2,[19][20][21][22][23], we found a statistically significant correlation of Ki-67, PCNA and MCM2 PI in advanced gastric cancer with local lymph node involvement. The mean proliferation indices for Ki-67 and PCNA were higher in gastric cancer with local lymph node involvement.…”
Section: Discussionsupporting
confidence: 59%
“…Patients with high PCNA PI in early gastric carcinoma much more frequently have lymph node metastases. Moreover, the postoperative survival time of patients with high PCNA PI in gastric carcinoma is considerably shorter than in the case of low PCNA PI in tumour tissue [23,25]. Mûller et al [15] observed no difference in the length of postoperative survival between patients with low and high Ki-67 index.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…None of the gastric carcinomas with negative immunoreaction for p21 waf1 exhibited lymph node metastasis, and there was a higher frequency of lymph node involvement in cases with greater positivity for p21 waf1 , as previously documented (17,25). It was observed that 65.4% of the cases were positive for p21 waf1 , and a higher incidence of lymph node involvement was also found in patients with increased proliferative activity and loss of expression of p21 waf1 in tumor tissue (26).…”
Section: Kip1supporting
confidence: 77%
“…44 However, low p21 Waf/Cip1 and p27 Kip1 expressions have been reported in gastric cancers and related cancer progression. 45,46 Activation of the MAPK and NFjB pathway is associated with gastric cancers and development. 47,48 Therefore, increased Id-1 expression may contribute to gastric cancer development by regulating these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%